Synthesis, characterization and optimization of chicken feather-based keratin biopolymers - Basma Yahya Muaydh, Ahmed Alashwal (2022)
Every year, large amounts of feather waste are generated from chicken meat consumption, posing a threat to environmental safety and human health. However, keratin protein found in chicken feathers can be used to make a variety of eco-friendly products, including biopolymers. As a result, they benefit the environment by reducing the uses of synthetic plastics. The current research aimed to clean the chicken feathers and extract the keratin protein for producing keratin-based biopolymer. Accordingly, two different cleaning agents were used to clean chicken feather waste in the pretreatment processes. Additionally, four parameters were chosen to optimize the keratin extraction process from cleaned chicken feathers using response surface methodology (RSM): reducing agent concentration (NaOH) (0.5–1.5N), temperature (45–75°C), mixing time (3–7 hr), and pH (10–13). On the other hand, the optimal conditions for the synthesis of biopolymers were determined using response surface methodology (RSM) with three selected parameters, including keratin concentration (3-6 g/ml), mixing temperature (55-65°C), and drying time (36- 60hr). The keratin/cellulose-based biopolymer (KC-60) were synthesized using the same conditions as the keratin-based biopolymer (K-60), and their properties were compared under specific characterization conditions, with (PVA) and glycerol serving as the study primary biopolymer and plasticizer. The result showed that the cleaning by detergent with bleaching agent help increase the keratin yield with high purity compared to detergent and bleaching. The optimal conditions for keratin extraction were 1N NaOH at 60°C temperature for 5 hours of mixing time, based on the error (%) of RSM modelling. The functional groups of extracted keratins were investigated using Fourier-transform infrared spectroscopy (FTIR), the elements of keratin were quantified using EDX, the surface morphology of keratin was examined using a scanning electron microscope (SEM), and the crystallinity of keratin protein was determined using X-Ray Diffraction (XRD). Moreover, the model determined the optimal conditions for the best formation of the biopolymer using 6 g/ml keratin for 70 minutes of mixing time and 60 hours of drying time, resulting in a film with the highest actual value tensile strength 8.29 MPa and a sample accuracy error of 0.72 %. The FT-IR analysis of the K-60 and KC-60 biopolymer confirmed the presence of the keratin and microcrystalline cellulose functional groups. In comparison, scanning electron microscopy (SEM) was used to characterize the surface morphology, while X-ray diffraction revealed the films' crystalline structure. X-ray diffraction (XRD) analysis confirmed the prepared biopolymer's robust crystalline structure. Additionally, thermogravimetric analysis (TGA) of (K-60) and (KC-60) demonstrated that increasing the temperature increased the cross- linking efficiency of cellulose and keratin. Mechanical properties indicate that the K-60 sample exhibits momentous values of tensile strength and Young's modulus to 3.64 MPa and 1.4 MPa higher than the KC-60 sample. The degradations, moisture and solubility tests revealed that the K- 60 biopolymer was relatively higher than KC-60 with 10%, 6.4% and 9.6% and they broke at a specific period. The distinctive properties of keratin protein contribute to its efficacy in the synthesis of keratin-based biopolymers in laboratory and industry.